Pendampingan Kader Lansia dalam Edukasi Kram Perut dengan Kompres Hangat pada Daerah Perut - Rustam Aji Rochmat; Dewi Lusiani; Wiwiek Mulyani; Sherly Ratih Frichesyarius Santi Ajhie; Roro Ajhie Ayuningtyas; Indah Fitri Andini (CV. CENDIKIA JENIUS INDONESIA, 2025)
This community service activity aimed to improve the knowledge and skills of elderly health cadres in providing first aid for abdominal cramps using a warm compress. The implementation method included health education through interactive lectures, discussions, and live demonstrations of warm compress techniques, followed by participant practice under facilitator guidance. The target audience consisted of six elderly health cadres and twenty-one elderly participants from the “Sekolah Lansia Tangguh” (Resilient Elderly School) in Dusun Curup Village, Rejang Lebong Regency. The results showed that after the counseling and practice sessions, 2 out of 6 elderly cadres (33.3%) and 4 out of 21 elderly participants (19.0%) were able to correctly demonstrate how to relieve abdominal cramps using a warm compress. In conclusion, education and mentoring for elderly health cadres have the potential to enhance community capacity in applying warm compresses as first aid for abdominal cramps. It is recommended that similar activities be carried out continuously to broaden the reach of knowledge and skills within the community.